2023
DOI: 10.1371/journal.pone.0285197
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss efficiency and safety of tirzepatide: A Systematic review

Abstract: Objective Tirzeptide is a novel glucagon-like peptide-1 receptor (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) drug, which shows good efficiency for weight loss. Therefore, we aim to investigate the efficacy and safety of tirzepatide for weight loss in type 2 diabetes mellitus (T2DM) and obesity patients in this meta-analysis study. Methods Cochrane Library, PubMed, Embase, Clinical Trials, and Web of Science were searched from inception to October 5, 2022. All randomized controlled trials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…These reactions are not signi cantly different from those caused by GLP-1RAs. Additionally, gastrointestinal reactions to TZP tend to decrease over time [39][40][41][42] . Simultaneously, the use of TZP signi cantly increased the incidence of gallbladder and biliary diseases, but did not elevate the risk of pancreatitis [43] .…”
Section: Discussionmentioning
confidence: 99%
“…These reactions are not signi cantly different from those caused by GLP-1RAs. Additionally, gastrointestinal reactions to TZP tend to decrease over time [39][40][41][42] . Simultaneously, the use of TZP signi cantly increased the incidence of gallbladder and biliary diseases, but did not elevate the risk of pancreatitis [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Mounjaro® is available in the following doses: 2.5 mg, 5 mg, 7.5 mg, 10 mg, 12.5 mg, and 15 mg [ 32 ]. In pharmacokinetic studies, it was found that the mean half-life was 116.7 h (5 days); hence, the most optimal and practiced form of dosing is weekly subcutaneous injections of the drug [ 29 ].…”
Section: Tirzepatidementioning
confidence: 99%
“…Three systematic reviews and meta-analyses have been published in 2023, documenting the weight loss benefits of tirzepatide (Lin et al, 2023;Rohani et al, 2023;Tan et al, 2023), with one drawing attention to the need for vigilance regarding gastrointestinal adverse effects (Lin et al, 2023).…”
Section: Dual Incretin Agonistsmentioning
confidence: 99%